THE LEARNING STYLE OF MILLENIAL STUDENTS AT ENGLISH EDUCATION DEPARTMENT OF IAIN BUKITTINGGI - Ummu Hani; Leli Lismay (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2020)
This research was conducted based on some problems found related to the learning style of milenial students in the classroom interaction. Most of the students did not follow the instructions given by the lecturer when working on assignment. So that, analysing milenial learning style is needed in order to found out some appropiate styles and strategies in teaching. This research was qualitative research. The instrument used in this research was observation and interview. The result showed that there were three categories of millenial learning styles namely; team learning, experiencing, and uses technologies in learning. Especially for students in the 2nd year at English Education Department of State Islamic Institute of Bukittinggi, Most of the students applied  team learning and uses technologies as learning styles during classroom interaction. They did not like the style of experiencing, while in the language classroom, experincing, should be the crucial factor to help the students mastering the target language. In coclusion, millenial learning styles at English Education Department of State Islamic Institute of Bukittinggi need to be improved in order to achieve the learning objectives.Keywords: Learning Style, Millenial, classroom interaction.